1993
DOI: 10.1111/j.1746-1561.1993.tb06087.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Condom Use and Number of Sexual Partners Among High School Adolescents

Abstract: Factors associated with condom use and number of sexual partners were examined in a statewide sample of public high school students in grades 9-12 (N = 3,893). Data were collected in spring 1990 using the 70-item, self-report Youth Risk Behavior Survey, developed and piloted by the Centers for Disease Control. Composite scores were constructed to measure aggression, physical recklessness, alcohol use, illegal drug use, cigarette use, lack of exercise, and academic self-image. Since simple polychotomous logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 16 publications
4
40
0
6
Order By: Relevance
“…This finding is in agreement with 1992 NHIS (National Health Interview Survey) in US that showed no relationship between condom use and the number of sexual partners among 12-21 year old from sampled households as reported by Santelli et al [16] and Ritchter et al [17] which showed a negative association. Contrary to the reports of Svare et al [5][6][7]18] which showed positive association between multiple sexual partners and condom use.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with 1992 NHIS (National Health Interview Survey) in US that showed no relationship between condom use and the number of sexual partners among 12-21 year old from sampled households as reported by Santelli et al [16] and Ritchter et al [17] which showed a negative association. Contrary to the reports of Svare et al [5][6][7]18] which showed positive association between multiple sexual partners and condom use.…”
Section: Discussionsupporting
confidence: 82%
“…Mas mesmo com este aumento nos últi-mos anos, deve-se observar que o uso desse método não se mantém nos mesmos percentuais quando comparamos dois eventos, no caso a primeira e a última relação sexual. O uso do preservativo cai significativamente na últi-ma relação sexual, particularmente entre as mulheres, que também o utilizam num percentual menor que os homens na iniciação 1,12,15,16 .…”
Section: Discussionunclassified
“…Males were more than 12 times more likely to have had six or more lifetime partners if they had engaged in sexual intercourse before 14. A negative relationship between number of sexual partners and condom use has also been established, with condom use declining as number of partners increases (Richter, Valois, McKeown, & Vincent, 1993).…”
mentioning
confidence: 99%